Hanyu Shuiping Kaoshi (HSK) serta Kaitannya dengan Kemampuan Bahasa Mandarin - , RIYANA ISTIQOMA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
HSK (HÃ nyÅ ShuÄpÃng KÄoshÃ¬) is the same as TOEFL for English, HSK is used to examine the ability of Chinese. HSK is a set of test for non-native mandarin Chinese language learners. Itâs not only examine the ability of oral communication , but also test the ability of Chinese handwriting and writing skill. HSK is a set of test which is organized by Chinese Hanban and foreign institutions which is approved by Hanban. This essay â The Relationship Between HSK and Mandarin Language Skillâ is aim to clarify the importance of HSK for non-native mandarin Chinese language learners and the objectivity of HSK grades which are used to judge the ability of Chinese language. HSK grades are very important for non-native mandarin Chinese language learners. Itâs not only the bargaining chip for them to apply for a job in government, business and other field, but also the qualification of further study in China, particularly for Chinese national scholarship application. Therefore, to obtain HSK certification has become a necessary condition in above-mentioned matters.